Investigation of the Economic Mechanism of Utilizing Distributed Solar Photovoltaic Systems in Iran - Sana Labbafi; Sina Labbafi; Hossein Heirani; Seyedali Sina (International Journal of Photoenergy)
Today, the utilization of small-scale solar systems for houses has increased significantly around the globe. The rise of electricity prices due to elevated prices of fossil fuels coupled with the global concerns about the increased emission of greenhouse gases has fueled the increased application of renewable energy systems. However, such policies have been ineffective in particular countries where the electricity prices are kept too low to control social atmosphere and enhance the people’s well-being for political purposes—in this case, solar systems have witnessed no growth as they have rendered not economically justifiable. In this respect, the present research considers Iran as a country with very low electricity prices coupled with very large potentials for utilizing solar energy in the presence of imbalanced electricity supply and demand, with the research objective being an investigation of the required incentive policies to promote the utilization of distributed solar photovoltaic (DSPV) systems in the country. According to the results, it was figured out that, under the current conditions, escalating the price of electricity for houses (even to as high as 10 times the current prices) cannot cover the costs of the equivalent DSPV systems, indicating a need for another cluster of policies. As an option, one may consider buying the generated electricity by the customer (from renewable sources) at a higher price than that at which the electricity is offered to households via the grid (by a margin of 15 folds), which is supposed to provide the required incentive to expand the utilization of DSPV systems.